2009
DOI: 10.1007/s11144-009-0122-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cr doping on the properties and photocatalytic activity of Bi12TiO20

Abstract: Undoped and Cr-doped Bi 12 TiO 20 (BTO) were prepared and used as photocatalysts for the degradation of formic acid both under visible light and UV irradiation. The effects of the Cr doping on the visible light response and the photocatalytic activity of BTO were investigated. The prepared catalysts were characterized by using XRD, XPS, UV-Vis diffuse reflectance spectroscopy (DRS) and photoluminescence (PL) spectroscopy. The doping of Bi 12 TiO 20 with low concentration of Cr leads to noticeable increase in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…At Cr contents greater than 1.47 wt%, the photoluminescence intensity begins to increase. The photoluminescence emission, mainly resulting from the recombination of photoinduced charges, i.e., electrons and holes, has been generally used to measure the efficiency of charge carrier trapping, migration, and transfer in the semiconductor powders [44,45] as well as films [46][47][48]. Furthermore, it is generally accepted that the photoluminescence intensity is closely related to the probability of charge recombination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At Cr contents greater than 1.47 wt%, the photoluminescence intensity begins to increase. The photoluminescence emission, mainly resulting from the recombination of photoinduced charges, i.e., electrons and holes, has been generally used to measure the efficiency of charge carrier trapping, migration, and transfer in the semiconductor powders [44,45] as well as films [46][47][48]. Furthermore, it is generally accepted that the photoluminescence intensity is closely related to the probability of charge recombination.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that transition metal ions doped into powder photocatalysts can increase the quantum efficiency of heterogeneous photocatalytic reaction by acting as electron (or hole) traps and by altering the electron-hole pair recombination rate [49,50]. It has been shown that doping Bi 12 TiO 20 with low content of Ba 2 + or Cr 3 + can significantly increase the photocatalytic activity, which is attributed to an alteration of the electron-hole pair recombination rate [44,51]. As shown in Figure 5(a), doping Cr into a-Fe 2 O 3 nanorod films at a low content helps to inhibit the recombination of photogenerated electron-hole pairs, which is reflected as increased PEC performance for water splitting.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, sillenite-type materials have been widely applied in a number of applications such as optical data processing and storage, electro-optics, acoustics, peizotechnics, optoelectronic, electronics, fiber optic sensor, image amplification, real-time and multiwavelength hologram imaging, metrological problems, and a variety of photocatalysis applications [46][47][48][49][50]. Bismuth oxide crystals with the sillenite structure, as defined by the general formula Bi 12 [M]O 20 (BMO), where M is the tetravalent ion of the elements from II-VIII groups of the Periodic Table, are a body-centered cubic crystal structure with the space group I23 [51][52][53]. Figure 1 shows the crystal structure of the perfect Bi 12 MO 20 sillenite and local structure around the Bi and the M sites.…”
Section: Bismuth Sillenite Crystalsmentioning
confidence: 99%